2019
DOI: 10.1055/s-0039-1690757
|View full text |Cite
|
Sign up to set email alerts
|

An Iodide-Mediated Transition-Metal-Free Strategy towards Unsymmetrical Diaryl Sulfides via Arylhydrazines and Thiols

Abstract: A mild, scalable iodine-mediated oxidative cross-coupling reaction of arylhydrazines and thiols for construction of thioethers (sulfides) in the absence of any transition metals or photocatalysts is disclosed. A variety of unsymmetrical diaryl sulfides with broad substrate scope both on thiols and hydrazines were synthesized in high yields in water at room temperature. Furthermore, to demonstrate the utility of the protocol, the above C–S bond formation was applied in the synthesis of the key structure of vort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…They utilized TBHP as an oxidant and KI as an additive in this reaction (Scheme 46). [70] Joussef et al reported the synthesis of diaryl sulfides through C (sp 2 )-H bond sulfenylation of (hetero)arenes using a KIO 3 /ethylene glycol catalytic system. Several of the sulfurated (hetero)arenes revealed a high percent of AChE inhibition, revealing their potential anti-Alzheimer activity.…”
Section: Metal-free Processes In S-arylation Reactionsmentioning
confidence: 99%
“…They utilized TBHP as an oxidant and KI as an additive in this reaction (Scheme 46). [70] Joussef et al reported the synthesis of diaryl sulfides through C (sp 2 )-H bond sulfenylation of (hetero)arenes using a KIO 3 /ethylene glycol catalytic system. Several of the sulfurated (hetero)arenes revealed a high percent of AChE inhibition, revealing their potential anti-Alzheimer activity.…”
Section: Metal-free Processes In S-arylation Reactionsmentioning
confidence: 99%
“…It is interesting that pentafluorobenzoic acid was dithiolated under the optimal condition. In 2019, the Jafarpour group reported a simple procedure for the synthesis of unsymmetrical diaryl sulfides from arylhydrazines and aryl thiols (Scheme 25) [45]. The reaction proceeded at room temperature in the presence of TBHP, KI, and Cs 2 CO 3 in water, providing the corresponding sulfides in good yields.…”
Section: C(sp 2 )-S Bond Formation With Thiolmentioning
confidence: 99%
“…Treatment of the benzyne generated in situ from 2-(trimethylsilyl)phenyl triflate (using excess CsF) with N-Boc-protected 1-[(2,4-dimethylphenyl)thio]piperazine in DME as solvent, followed by deprotection led to the formation of vortioxetine. In 2020, Jafarpour et al 7 reported an iodine-mediated oxidative cross-coupling reaction of arylhydrazines and thiols for construction of thioethers in the absence of any transition metals or photocatalysts and this method was applied in the synthesis of the key structure of vortioxetine.…”
mentioning
confidence: 99%